Pa'boya: The Adaptation of Coastal Communities in South Sulawesi to Maritime Migration Policies in Southeast Asia - Tita Andraena; Imam Fadhil Nugrah (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
Migration has long been a significant characteristic of human societies, shaping demographic patterns, socio-economic structures, and cultural landscapes across regions. In Southeast Asia, migration is driven by diverse factors such as labor demands, environmental challenges, and socio-political instability. This study focuses on the adaptation strategies of coastal communities in South Sulawesi, particularly the Pa’boya community, in response to maritime migration policies. These communities face dual challenges from regional migration policies and environmental changes, which impact their cultural identity, traditional livelihoods, and access to natural resources. The research adopts a qualitative methodology, analyzing secondary data from journal articles, books, and policy documents. The study explores the relationship between local adaptation mechanisms, such as the Pa’boya's cultural practices, and broader regional policy frameworks. It also highlights the gaps in existing migration policies that often fail to address the unique challenges faced by coastal communities. The results show that the Pa’boya community has developed sophisticated responses to migration policies through collective action, advocacy, and the preservation of cultural heritage. Despite policy restrictions that affect traditional fishing practices, the community demonstrates resilience by diversifying livelihoods and engaging in sustainable practices. However, the impact of modernization and environmental pressures poses risks to their cultural identity, and there is an urgent need for policies that integrate local perspectives into broader migration frameworks.